On the efficacy of construction site safety inspections - Emery, H; Gordon, D.V; McClintock, Doug (School of Management Working Papers, 1995)
The purpose of this paper is to measure the impact of onsite safety inspections on the frequency of work related injuries in the Alberta construction sector for the period 1987 to 1992. The data are disaggregated by sub-industry allowing different risk levels to be associated with different work activities. In addition, within the sample period there is a dramatic decrease in inspection activity providing a natural experiment into the necessity of continued inspection effort. We observe no measurable effect of onsite safety inspections altering the risk of accident and injury. Moreover, the decrease in inspection levels within the sample period is not associated with an increase in the number of work related injuries.